Reflective Writing Method with the Assistance of the ‘Writing Friends’ Podcast to Improve High School Students' Narrative Writing Skills - Widiyarto, Sigit; Pujaning Ati, Aster; Megayanti, Windi (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: This research aims to explore the implementation process of the reflective writing method, with the assistance of the 'Writing Friends' podcast, in high schools. It identifies integration steps in the classroom and determines the effectiveness of this combination in enhancing students' narrative writing skills. Method: The study employs classroom action research through two cycles. Results: The average score of students' narrative writing skills was 65 out of 100, reflecting a moderate level of competence. Many students struggled, particularly with story coherence and character development, as well as to some extent with grammatical accuracy and punctuation. The steps of the reflective writing method include: first, selecting a meaningful personal experience; second, drafting an initial story that expresses thoughts and feelings related to the experience; third, exchanging the draft with friends or peers who can provide constructive feedback; and finally, sharing the polished story with others or keeping it as a personal reflection. Novelty: This research enhances storytelling, self-awareness, confidence, and critical thinking in language teaching. It also contributes new knowledge by demonstrating how this specific integration fosters interconnected writing practices, promoting the comprehensive development of writing skills among high school students.